The study of water quality change at Sai Noi Floating Marketing, Phra Phimonracha canal, Sai Noi district, Nonthaburi province - ปาลิเอกวุฒิ วันทิตา; มโนคุ้น ปิติพร (RMUTSB ACADEMIC JOURNAL, 2018)
Phra Phimonracha canal was the main water consumption source for the Sai Noi community in the past. The urbanization has recently expanded among this area and has been promoted as tourist attraction namely Sai Noi Floating Market (approximately 400 m of canal length), which is the sampling site of this study. The result comes from collected and monitored water quality during 6 months (February to July, 2016). The water quality was measured by 8 indexes by the physical, chemical and biological parameters, which the results of physical quality showed that the total solid (TS) and turbidity found 337.5-1,350 mg/L and 26.5-120 NTU, respectively. The range of pH was 6.8-7.8. The oxygen demand (DO) and the biological oxygen demand (BOD) showed in range of 3.00-8.35 mg/L, respectively. The contaminants cause eutrophication which are nitrate (NO3-) and phosphate (PO43-) found in range of 0.05-0.25 mg NO3-/L and 0.34-0.75 mg PO43-/L. Moreover, the result of total coliform bacteria showed in range of 47.50-12,350 mpn/100 mL. The situation over 6 months of this study can be concluded that Phra Phimonracha canal in area of Sai Noi Floating Market is defined as the 3rd level by the Environmental Quality Act B.E. 2535 that refers to fair quality of surface water. For consumption as water supply, the water quality in study area must be improved. While utilization for agriculture is allowed.